Analisis Faktor-Faktor yang Mempengaruhi Perilaku Keuangan Pemain Game Online Roblox pada Generasi Z di Indonesia - Nisrina Hesi Rahmaningtyas; Agus Prayitno; Dwi Eko Waluyo; Suhita Whini Setyahuni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The rapid development of digital technology has significantly transformed consumption patterns among Generation Z, particularly within online gaming ecosystems such as Roblox. The platform encourages repeated virtual spending through its in-game currency system, making it relevant to examine how psychological and technological factors shape users' financial behavior. This study investigates the influence of Fear of Missing Out (FOMO), Financial Literacy, and Financial Technology (FinTech) on the financial behavior of Generation Z Roblox players in Indonesia. A quantitative research design was employed, with data gathered from 219 respondents selected through purposive sampling. The analytical method used was Structural Equation Modeling–Partial Least Squares (SEM-PLS) via SmartPLS 4 software. The findings indicate that Financial Literacy and FinTech adoption positively and significantly affect financial behavior, while FOMO shows a negative but statistically insignificant effect. The income variable (Benefit) used as a control also did not significantly influence financial behavior. The model achieved an R-square value of 0.632, suggesting that the independent variables collectively explain 63.2% of the variance in financial behavior. These results highlight the importance of financial education programs and the strategic use of digital payment tools in fostering responsible financial habits among young gamers.